The Influence of the Digital State on Preventing and Detecting Corruption in Ukraine - KOBETS, Yuliia; DIAKUR, Mariia; KYSLYI, Anatolii; SHULGA, Marina; TOROPCHYNA, Iryna (Theoretical and Practical Research in Economic Fields, 2024)
The impact of state processes digitalization on preventing and detecting corruption in Ukraine is a key aspect for understanding the effectiveness of governance and the development of modern strategies in the fight against corruption. The utilization of digital technologies has the potential to substantially enhance transparency and diminish corruption hazards within governmental frameworks. The purpose of the article is to examine this effect in relation to contemporary challenges and opportunities. The article demonstrates that digital systems integration, such as e-declaration and e-procurement, assists in mitigating prospects for corrupt practices and increases citizens' trust in government. Correlation analysis shows the relationship between digitalization level and anti-corruption measures’ effectiveness, emphasizing the importance of technological innovations in public administration. The obtained results of the correlation analysis show a connection at the level of 0.438, which indicates a moderate positive correlation between digitalization level of government processes and corruption decrease. The recommendations point to the need for an integrated approach where digital intervention is combined with other anti-corruption measures, including legal reforms and public engagement, to attain more substantial outcomes in the fight against corruption. The conclusions of the article highlight the significance of advancing digital infrastructure and legislative support for digital initiatives. The article draws attention to the imperative need to integrate digital strategies with the comprehensive anti-corruption policy in order to maximize their effectiveness and positive impact on society.